(untitled) (Vietnam Journal of Community Medicine, 2024)
Ear keloids is one of the most common forms of keloid, which may cause pain, itching, and unaesthetical appearance. Ear keloids are firm, rubbery, fibrous nodules that form on the ear after superficial or deep cutaneous trauma such as operations, ear piercing, trauma, burns and some cutaneous disorders. They can occur in earlobes as well as in the skin and cartilage higher on the ear. Despite a variety of treatment options, recurrence is common. We report a case of a 29 years old female, having left ear keloid after 1 year of traffic accidents. This case report presents a combination of reconstructive surgery (excision and instant reconstruction based on the reconstructive ladder) to treat giant ear keloid to reduce the recurrence rate and achieve better clinical results.